(3GdMGhjs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3TcQ Gddg Hf CHj GdNjQ Hf CHj SYjO GdUOjbi s)
(3ChdgG (B:s
(3Chd GdeLdO GdChd gPG cJGH Cdag eMeO Hf RcQjGA GdQGRi GdeJWHH ai GdWH , LeY ajg GdCeQGV GdcdjI ai HOf GdEfSGf heYGdLGJgG s
(3BNQgG (B:s
(3hjfJgi HBNQ GdUOGY hZaQGf LRA HYO Cf jfbM HeGA GdhQO hfMd hjTQH Ydi GdYWhQ hcd ef OhGe Ydi TQHg Sde Ef TGA Gddg JYGdi s
(3bQf GdfSN (B:s
(3GdbQf GdYGTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdWH (B- (3bSe GdcJGH GdChd (B; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B628s
(3eUOQ GbJfGA GdCUd (B:s
(3ecJHgi TgjO Ydi (B(2081(2)) s
Keywords: (3GdWHs